Seroprevalence of Human Herpesvirus Infections in Newly Diagnosed HIV-Infected Key Populations in Dar es Salaam, Tanzania - Doreen Kamori; Agricola Joachim; Mucho Mizinduko; Godfrey Barabona; Macdonald Mahiti; Upendo Kibwana; Mtebe Majigo; Salim Masoud; Ambele M. Mwandigha; Takamasa Ueno; Elia Mmbaga; Eligius Lyamuya (International Journal of Microbiology)
Background. Human herpesvirus (HHV) infections can significantly increase the risk of human immunodeficiency virus (HIV) transmission and accelerate disease progression. In the population at high risk of HIV infection, also termed as key populations (female sex workers (FSW), men who have sex with men (MSM), and people who inject drugs (PWID)), and their sexual partners, HHV infections can potentially compromise the efforts to prevent and control HIV infection. Here, we investigated the seroprevalence of HHV infections among HIV-infected key populations in Dar es Salaam, Tanzania. Methodology. We analyzed 262 archived serum samples of HIV-infected key populations from the integrated biobehavioral surveillance (IBBS) study conducted in Dar es Salaam, Tanzania. The enzyme-linked immunosorbent assay was used to determine IgG and IgM titers for cytomegalovirus (CMV) and herpes simplex virus (HSV) types 1 and 2. Results. The overall seropositivity of HHV IgG was 92% (95% CI: 87.7–95.3%). HHV IgM was not detected in any of the samples. The most seroprevalent coinfection was CMV at 69.1% (181/262), followed by HSV-2 33.2% (87/262) and HSV-1 32.1% (84/262). HSV-2 infection differed by key population groups; it accounted for FSW (46.3%) (p=0.0001) compared to PWID (21.6%) and MSM (22.7%). In contrast, seroprevalence for CMV and HSV-1 was comparable across the key population groups; whereby, CMV was 62%, 75.3%, and 75% and HSV-1 was 26.4%, 39.2%, and 31.8% for FSW, MSM, and PWID, respectively. We also observed that multiple coinfections with CMV-HSV-2 (p=0.042) and CMV-HSV-1-HSV-2 (p=0.006) were significantly associated with key population aged above 40 years. Conclusion. The IgG seroprevalence of CMV, HSV-1, and HSV-2 was high among HIV-positive key populations. These findings indicate that these individuals are prone to recurrence of HHV infections and may harbor replicating viruses that subsequently may affect HIV disease progression. Therefore, this warrants concerted efforts for integrated HIV and sexually transmitted infection prevention programs targeting key populations.